PELATIHAN PIJAT LAKTASI BAGI BIDAN DI KOTA PEKANBARU TAHUN 2020 - Septi Indah Permata Sari; Siska Helina; Juraida Roito Hrp (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The presentation of exclusive breastfeeding in Indonesia in 2018 decreased in 2019, this figure was below the national target of 80%. The new method introduced to overcome problems in breastfeeding is Lactation Massage, which is effective in overcoming problems that arise during breastfeeding. The purpose of this activity is to provide lactation massage training for midwives in Pekanbaru City. This activity was carried out online for 16 midwives who work in pratama and PMB clinics in Pekanbaru City. Implementation time for 8 months. The implementation method consists of Pre-test, Massage Training, Evaluation of massage and Post-test. This activity was carried out for 8 meetings. The results of the activity showed an increase in the average knowledge of Midwives from 56 to 75. The evaluation of skills through video was good. It is recommended to carry out lactation massage training to midwives on an ongoing basis with a larger number of participants.